Pembelajaran Pendidikan Agama Islam (PAI) Model Keberagamaan Inklusif untuk Mencegah Radikalisme Beragama Dikalangan Siswa SMA - Abdurrohman, Abdurrohman; Syamsiar, Huldiya (LP2M IAIN Samarinda, 2017)
The phenomenon of religious radicalism has become a global threat of the 21st century that phenomenon was a result of Islam as anaccused religion and was often associated with a terrorist religion. Educational institutions often